Instrument Validity and Reliability Test of Attitude, Subjective Norm, and Intention to Pornography in Urban Students - Mubarokah, Kismi; Aprianti, Aprianti; Anggraini, Fitria Dewi Puspita; Zahra, Zakiyyatuz; Kadarsih, Luhur Asih (Health Science UDINUS, 2023)
The theory of planned behavior (TPB) has been proposed to be applied to the issue of pornography in urban student participants. The study aims to examine the validity and reliability of instrument attitudes, subjective norms, and intentions of students in consuming pornography. The instrument was tested on 1845 students by a self-administered online questionnaire. The collected data is then tested for validity with Pearson product-moment. The item question is valid if the r count > r table. Then the variable is reliable if the Cronbach alpha value is more than 0.60. A total of 5 attitude question items, four subjective norm question items, and six intention question items were all declared valid (CI: 95%; r value > 0.062). While Cronbach alpha values for attitude (0.769), subjective norm (0.676), and intention (0.863). This valid and reliable instrument can measure attitude, subjective norm, and intention on similar targets.